Populasi Bakteri dan Keberadaan Bakteri gram (+) dan (-) dalam Pellet Calf Starter yang Ditambah Limbah Kubis Fermentasi - S Mukodiningsih; B Sulistiyanto; SS Sholikhah (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2018)
The aim of the experiment was to evaluate total bacteria population and the existence of positive and negative gram bacteria of pellet calf starter which added by lactic acid bacteria from fermented cabbage waste. The materials in this research were corn, rice bran, soybean meal, mineral mix, molasses, fermented cabbage wasted. The research was conducted by Completely Randomized Design with 4 treatments and 5 replications. The treatments were T0 (100% calf starter), T1 (2% of fermented cabbage waste + 100% calf starter), T2 (4% of fermented cabbage waste + 100% calf starter) and T3 (6% of fermented cabbage waste + 100% calf starter). The Variables observed were bacteria population and gram bacteria. Data of bacteria population were evaluated by descriptive analysis, while data of gram bacteria existence were statistically analyses by variance analysis, if there were significantly affect continued by Duncan test. The results showed that the highest bacteria population was on the treatment with addition level 2% of fermented cabbage waste and the lowest bacteria population was on addition level 6%. Adding fermented cabbage waste did not significantly effect to the existence of gram bacteria. The average score of gram bacteria existence on added fermented cabbage waste from level 0%, 2%, 4%, and 6% were respectively 1.99; 2.10; 2.29 and 2.29. Positive gram bacteria extended increased with increased fermented cabbage waste. The conclusion was the pellet calf starter which added with lactic acid bacteria produced bacteria and there was positive gram bacteria, and suppress negative bacteria. Keyword: bacteria population, fermented cabbage waste, gram bacteria, pellet calf starter